In Operando Atomic Force Microscopy Imaging of Electrochemical Interfaces: A Short Perspective. Issue 24 (21st December 2021) - Neupane, Shova; Valencia-Ramírez, Andrea; Losada-Pérez, Patricia; Renner, Frank Uwe
Abstract : Electrochemical Interfaces Fighting the degradation of materials clearly is an important endeavour for reaching a sustainable society. Controlled heterogeneity can be introduced onto a surface for example by microcontact printing. Subsequent in operando observation such as by atomic force microscopy allows fantastic insights. More details can be found in article number 2100470 by Frank Uwe Renner and co‐workers.